Schizophrenia or Possession? - Irmak, M. Kemal (Journal of religion and health, 2014)
Schizophrenia is typically a life-long condition characterized by acute symptom exacerbations and widely varying degrees of functional disability. Some of its symptoms, such as delusions and hallucinations, produce great subjective psychological pain. The most common delusion types are as follows: "My feelings and movements are controlled by others in a certain way" and "They put thoughts in my head that are not mine." Hallucinatory experiences are generally voices talking to the patient or among themselves. Hallucinations are a cardinal positive symptom of schizophrenia which deserves careful study in the hope it will give information about the pathophysiology of the disorder. We thought that many so-called hallucinations in schizophrenia are really illusions related to a real environmental stimulus. One approach to this hallucination problem is to consider the possibility of a demonic world. Demons are unseen creatures that are believed to exist in all major religions and have the power to possess humans and control their body. Demonic possession can manifest with a range of bizarre behaviors which could be interpreted as a number of different psychotic disorders with delusions and hallucinations. The hallucination in schizophrenia may therefore be an illusiona false interpretation of a real sensory image formed by demons. A local faith healer in our region helps the patients with schizophrenia. His method of treatment seems to be successful because his patients become symptom free after 3 months. Therefore, it would be useful for medical professions to work together with faith healers to define better treatment pathways for schizophrenia.